Savings of the Elderly and Desired Bequests - Hurd, Michael D. (American Economic Review, 1987)
Cross-section data often show that the wealth of the elderly increases with age even at advanced ages. These and other results suggest that the life-cycle hypothesis of consumption should be augmented to include a bequest motive for saving. In this paper, the author proposes a model of bequests, and a test for a bequ est motive. Using panel data, he finds that over a ten-year period the elderly in the data set dissaved, in contradiction to most cross- section results. The test offers no support for a bequest motive. Copyright 1987 by American Economic Association.